Ectoparasitic infestations among patients attending the dermatology OPD: A hospital-based study - Adhikari, Harihar; Gautam, Uttara; Rajput, Prabhat Singh; Basnyat, Subi; Marasini, Pawan; Sharma, Sandip Kumar; Maharjan, Sobi Lal (Journal of Karnali Academy of Health Sciences, 2024)
Background: Ectoparasites are organisms that live in the skin for varying lengths of time and can cause disease. These infestations are highly prevalent in poor and underdeveloped areas. There is a paucity of studies regarding their prevalence in rural areas like the upper Karnali region of Nepal. We conducted a hospital-based study to know the burden of these infestations in the area. Methods: A hospital-based descriptive study was done from March 2023 to February 2024. Data were collected from medical records of the dermatology outpatient department (OPD) and all the clinically diagnosed cases of ectoparasitic infestation were studied. Data were presented as frequency and percentage; seasonal pattern of the diseases was also reported. Results: A total of 6,698 patients attended dermatology OPD during the study period, among whom 1340 had ectoparasitic infestations, resulting in a proportion of 20.01% in this group. Two infestations were found, namely, scabies and pediculosis capitis, with a proportion of 18.36% and 1.65%, respectively. Females represented almost half of the patients with ectoparasitic infestations (49.63%), but about 98% with pediculosis. Ectoparasitic infestation was most common in children aged 0–9 years, i.e., 31.31% and pediculosis was most common in children of 10–19 years (31.81%). Ectoparasitic infestations (41.94%), both scabies (41.7%) and pediculosis (44.55%) were most common during the monsoon season. Conclusion: The ectoparasitic infestations were common the patients presenting to the hospital. Scabies was the most common ectoparasitic infestation and a major public health problem.